Assessment of efficiency and safety of complex therapy of acute adenoviral diseases in young people - N. A. Malyshev; N. I. Lvov; O. V. Maltsev (Лечащий Врач, 2021)
Retrospective analysis of medical histories of patients with adenoviral infection showed that therapy with inductor of «late» interferons kagocel significantly reduces the frequency of pneumonias development as well as protracted and recurrent disease course.